The role of the dietitian in the nutrition of physically active people using a group of footballers as an example - Sobek, Olga; Polaniak, Renata (Journal of Education, Health and Sport, 2022)
Introduction: Footballers often do not pay much attention to their diet. They get their knowledge about rational nutrition from various sources, most often from the internet. The person giving advice on nutrition is more often a coach than a professional nutritionist. Rational nutrition in combination with appropriate physical training allows for the desired sports results. Therefore, the role of a qualified nutritionist should be crucial. Aims and objectives: The aim was to investigate the knowledge and dietary habits of high-performance football players and to demonstrate the consequences of not eating a well-balanced diet. Material and methods: The study concerns a group of 100 people training football in sports clubs in the Silesian province. An original survey questionnaire was used to conduct them. Results were compiled using a Microsoft Excel spreadsheet. Results: Only 12% of respondents receive regular professional advice from a dietician. Despite this, only 41% of respondents declare a willingness to take advice from a dietician. Conclusions: The primary source of knowledge for football players is the internet and the coach. The unsatisfactory level of knowledge and poor eating habits are a consequence of the lack of care by a professional nutritionist in sports clubs.